TANTANGAN GURU DALAM PENYUSUNAN MODUL AJAR KURIKULUM MERDEKA: STUDI DI MADRASAH IBTIDAIYAH - Abaya, Rico (Titik Fokus Karya, 2024)
The research explores the challenges faced by teachers in preparing teaching modules for the Independent Curriculum (Kurikulum Merdeka) at MI Siti Mariam. The teaching module is a crucial element in Kurikulum Merdeka, serving as a guide for teachers in carrying out learning activities. The study aims to identify the difficulties teachers encounter in creating teaching modules and the efforts they make to overcome these issues. The research employed a qualitative case study approach, involving class teachers at MI Siti Mariam as the subjects. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, presentation, and conclusion techniques. The research findings highlight several teacher challenges in module preparation: difficulties in analyzing teaching needs, identifying the Pancasila Student Profile dimensions, defining teaching components, irregular module creation, and lack of training. To address these problems, teachers downloaded digital textbooks, self-studied Pancasila profiles, improved their pedagogical competencies, and engaged in self-directed learning to enhance module preparation skills.